The applications of management accounting techniques in Malaysian companies : an industrial survey / Ibrahim Kamal Abd Rahman, Normah Omar and Zubaidah Zainal Abidin - Abd Rahman, Ibrahim Kamal; Omar, Normah; Zainal Abidin, Zubaidah (Faculty of Accountancy, 2003)
In exploring the management accounting practices of companies in Malaysia, two categories of companies were chosen: Malaysian-Owned and Multinational corporations (MNCs). The majority of the companies selected were either manufacturing-based or service-based. To assess the level of management accounting applications in these organizations, Akira's "Four-Phase" model was adopted. While a "drifting phase" connotes an extremely low level of application, the "integrated phase" on the other hand deliberately uses the latest management accounting approaches for strategic purposes. Management accounting techniques surveyed include the applications of traditional methods such as Standard Costing, Budgeting and Cost-Volume-Profit (CVP) and other integrated approaches such as Just-in-Time (JIT), Activity-Based-Costing (ABC), Benchmarking and Target Costing.